Adherence to the Mediterranean Diet during COVID-19 national lockdowns: a systematic review. (20th October 2021) - Della Valle, PG; Mosconi, G; Nucci, D; Gianfagna, F; Iacoviello, L; Bonaccio, M; Odone, A
Abstract: Background: The Mediterranean Diet (MD) is one of the healthy eating plans recommended to promote health and prevent chronic diseases. During the COVID-19 pandemic, many countries adopted restrictive measures to mitigate infection spread, which might have influenced people's lifestyle and dietary habits. We conducted a systematic review to evaluate the impact of stay-at home orders' implementation on adherence to MD. Methods: Studies were identified searching Medline, Embase, and Web Of Science, the search strategy was developed using a combination of free text and mesh terms referring to COVID-19 pandemic, lockdown, and MD. Studies published until March 31st, 2021 were included. We only considered studies reporting original data from quantitative analysis and assessing modifications of adherence to the MD through validated dietary scores or any change in consumption of food categories that are typically ascribed to the MD. Data extraction, pooling and quality appraisal of the included studies, were conducted applying PRISMA guidelines. Results: 42 studies were retrieved. After duplicates removal, and in-blind two-step screening, 10 studies met our a priori defined inclusion criteria and were included in the review. 71.4% of the studies reporting a rate of change in adherence, measured through validated questionnaire both before and during lockdown, reported an increase, while 28.6% reported no significative changes. All included studies reporting the percentage of participants having a high adherence to the MD, based on their results on MEDAS questionnaire, before and during the lockdown, found an increase in this percentage. Conclusions: Adherence to the MD could have raised in people undergoing lockdowns due to COVID-19. Key messages: The impact of restrictive measures on determinants of health must be monitored. Despite the literature suggests adherence to MD has declined in the last years, this trend may have reversed or, at least, slowed during the initial phases of the current pandemic.